Impacto de los juegos didácticos con impresión 3D en el desarrollo de la motricidad fina en niños de Educación Inicial - Garcia Alvarado, Solange; Zamora Duran, Sharon (LACCEI, 2025)
This study analyzed the influence of didactic games created with 3D printing technology on the development of fine motor skills in five-year-old children from an early childhood education institution. The proposal focused on exploring innovative pedagogical resources that promote active learning during the early years. Using a quantitative approach and pre-experimental design, a purposive sample of 25 students was assessed with an observation guide before and after the intervention. The findings show that after using the games, the percentage of children at a high level of fine motor skills increased from 0% to 40%, while the low level decreased to 4%. The Wilcoxon test (p = 0.000) confirmed significant differences between pretest and posttest results, validating the effectiveness of the strategy. Notable improvements were observed in visual-motor coordination, manual coordination, and precision and control. These results demonstrate that integrating playful and technological resources can enhance children’s motivation and motor performance, providing valuable insights for teaching practice. It is recommended to replicate this strategy in other educational settings and continue adapting innovative materials to the needs of early childhood education.